Comparison of spontaneous mutagenesis level in children of both sexes with depressive disorders - Свідан, Інас Гхассан (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
The state of the chromosome apparatus was studied in patients of both sexes with depressive disorders. No significant differences in the frequency of spontaneous level of chromosomal abnormalities have been revealed in girls (12.6%) and in boys (13.59%) with depression, but a significant increase in the frequency of single and paired fragments has been registered in the karyotype of the boys (p<0.05) alongside with an elongation of centromeres of chromosomes 7, 10, 12 (group C) and deletion of the short arm in the karyotype of the girls (p<0.05). A comparison between the frequency of chromosomal abnormalities in girls and boys with depression and their frequency in the age-matched healthy children has revealed a significant increase in the disorders of chromatid, chromosome and genome types.